Pricing Analysis Through Online Travel Agents At JNG Hotel & Resort PT Langen Kridha Pratyangga - Kartiwa, Aa; Prayoga, Fauzan Huda; Dewi, Khisti Hanila; Jaja, Jaja (Journal of Bussines Management Basic, 2025)
The focus of this research is to analyze price setting through online travel agents, covering 4 dimensions: price affordability, price suitability with service quality, price suitability with benefits, and price according to ability or price competitiveness.The purpose of this research is to understand the optimization of pricing strategies across various Online Travel Agent (OTA) platforms in enhancing competitiveness.The informants in this study are the staff of PT Langen Kridha Pratyangga and the guests of Hotel JNG & Resort PT Langen Kridha Pratyangga.The method used in the preparation of this thesis is descriptive research with a qualitative approach.Data collection techniques were carried out through observation, interviews, documentation, and triangulation.In analyzing the data obtained, the Miles and Huberman model was used with the following steps: data collection, data reduction, data display, and conclusion drawing/verification.The results of this study indicate that the pricing through online travel agents at JNG & Resort PT Langen Kridha Pratyangga is quite good, but there are still indicators that need to be improved.Again, to improve the pricing through the online travel agent provided by the company